A Feasibility Study on Locally Manufacture Bone Screws and Bone Plates - Ingal, May (College of Engineering, 1997)
The feasibility study composed of a market study, a technical study, a financial study, a social profitability study, and an organization and management study on the production of locally manufactured bone screws and bone plates. This project is particularly made or an existing company, Orthopaedic Innovation Phils. Inc. (OIPI), manufacturing and distributing a wide range of implants. At present, the bone screw and bone plates, which are basic implants in the field of orthopedics are being imported and distributed by such companies as OIPI. The demand for the bone screws and bone plates was indirectly obtained from the Census of Bone Surgeries of accredited orthopedic hospitals in the Philippines. The supply data, on the other hand, were acquired from the interviews made with the suppliers' representatives. Correlating the demand and the supply with the population growth, the demand and supply forecasts for the next five years were derived. The volumes of demand and supply gap for 1998 for the seven products are: For the cortical screw, an excess supply of 8,578 units. For the Broad DCP, Narrow DCP, Mini DCP, and 1/3 Tubular Plate, excess supply of 708, 886 2,325, and 1,285 units respectively. For the cancellous screw and Semi-Tubular plate, a shortage supply of 1,635 units and 505 units. All values of supply and demand are increased 2% every year for the next 5 years. The market share percentage set for products with supply is greater than demand for 1998 is 15% - maintaining the existing market share, and it will increase 2% every year. For products with demand is greater than supply, the gap must be captured. It is expected that a considerable amount of market share will be captured in the next years reckoning on the idea that the company's selling prices for the said products will be 10% less than the lowest existing market prices. Supporting this is the proposed marketing strategy, characterized as resembling the marketing programs employed by the other suppliers but having some unique features and unique schemes on its own. Since the project is basically an addition of product lines, most of the current resources of the company were evaluated to check whether or not their unutilized portions are enough to provide the bone screw and bone plate production requirements. Fortunately, it was found that they are with the use of production and planning techniques as capacity planning and aggregate planning. For the capacity planning, it was evaluated that existing facility can produce the demand considering a 1.5% scrap rate. Manpower requirements were computed and were found out that eight workers are needed in the production area. For the aggregate planning, overtime was considered to meet the production requirements. The researchers evaluated the production schedule with 80% effective capacity and found out that for the next 5 years, production with overtime was sufficient to meet the production requirements. The project will produce 2,574 bone plates and 15,976 bone screws in 1998. For the other resources, certain criteria were initially set and with these as the bases of evaluation, it was assessed that there is no problem with regards to the availability of needed raw materials, supplies, and labor. The raw material, 360LVM will be purchased in Sandvik Bioline located at Sucat, Paranaque. A combination of these resources was drawn up to meet the production requirements determined in the market study. At the financial study part, the total project cost was computed and was found out to be P6,938,176.41 Proforma financial statements namely Income Statements, Cash Flows, and Balance sheet, for five years were prepared. For 1998, Income after taxes will be P123,101.03. The ending cash balance will be P4,773,782.91. The total assets for the year 1998, will be P7,061,278.27. Using the entries and numerical outcomes, financial analysis composed of financial ratios and sensitivity analysis techniques was done. From the results, the project's profitability, liquidity, and growth over time were proven. Before this of course, the soundness of investing on the project was assured using both non-time value and time value methods of evaluating investments. Specifically, the payback period is 3.54 years. NPV is positive amounting to P56,574.38, and the computed IRR is 16.758% which is greater than the 16% set MARR. In the Organization and Management Study, the company's form of ownership and organizational structure were analyzed. Its form of ownership is sole proprietorship and it need not be changed to another form with the addition of bone screw and bone plate product lines. Aside from modifying the present organizational chart due to the additional ten administrative and production personnel, the particulars of the job requirements, wages and benefits were also discussed. Lastly, it was briefly explained at the Social Profitability Study how this project, if it pushes through will affect the entire economy. With the use of local resources, such as labor, and some supplies, employment and income will be generated, thereby contributing to the livelihood of affected individuals. Taxes remitted to the municipal government region where the plant is located and national government will contribute to the attainment of community development. Because the products are import substitutes, foreign exchange savings can also be achieved. All of these have been quantified by incorporating the current tax rates with the cost-information at the financial study.